2018
DOI: 10.1002/arch.21510
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory attraction mediated by the maxillary palps in the striped fruit fly, Bactrocera scutellata: Electrophysiological and behavioral study

Abstract: Here, we report that the olfactory attraction of the striped fruit fly, Bactrocera scutellata (Hendel; Diptera: Tephritidae), a serious pest of pumpkin and other cucurbitaceae plants, to cue lure and raspberry ketone is mediated by the maxillary palps. The antennae, bearing three morphological types (basiconic, trichoid, and coeloconic) of olfactory sensilla, in male and female B. scutellata exhibited significant electroantennogram (EAG) responses to a plant volatile compound, 3-octanone, and methyl eugenol, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Similar to the antennal olfactory sensilla, the basiconic sensilla on the maxillary palpsin B. depressa are likely to be specialized into different functional types although they all show the same morphological features so that each functional type of sensilla can detect a narrow range of volatile compounds. This assumption is supported by recent reports on two Bactrocera species, showing that male-specific olfactory sensilla specialized for their parapheromone compound are present in the maxillary palps (Park, Jeong, Kwon, & Oh, 2018;Verschut et al, 2018).…”
Section: Olfactory Sensilla On the Mpbssupporting
confidence: 72%
“…Similar to the antennal olfactory sensilla, the basiconic sensilla on the maxillary palpsin B. depressa are likely to be specialized into different functional types although they all show the same morphological features so that each functional type of sensilla can detect a narrow range of volatile compounds. This assumption is supported by recent reports on two Bactrocera species, showing that male-specific olfactory sensilla specialized for their parapheromone compound are present in the maxillary palps (Park, Jeong, Kwon, & Oh, 2018;Verschut et al, 2018).…”
Section: Olfactory Sensilla On the Mpbssupporting
confidence: 72%
“…The maxillary palps of B. tryoni responded strikingly to cue-lure, whereas only a weak response was observed in the antennae [53]. Likewise, the maxillary palps also exhibited remarkable electrophysiological responses to cue-lure as well as RK in another RK-sensitive striped fruit fly, Z. scutellata [54]. The maxillary palps of both males and females responded to cue-lure in B. tryoni and Z. scutellata, suggesting that the male-specific attraction is triggered by sexually dimorphic processing of chemosensory information in the central nervous system, rather than in the peripheral tissues, in these species.…”
Section: Detection Of Male Attractants By the Peripheral Sensory Organsmentioning
confidence: 96%
“…Identifying the organ involved in the detection of male attractants is of much interest. Notably, recent studies have demonstrated that male attractants are detected not only by the antennae, but also by the maxillary palps, entailing different effects among fruit fly species [52][53][54]. For ME-sensitive B. dorsalis, ablation of male antennae remarkably reduced responsiveness to ME at a short range [52].…”
Section: Detection Of Male Attractants By the Peripheral Sensory Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methyl eugenol is known to induce an electrophysiological response in medfly [ 302 ]. In Z. scutellatus , ME elicits significant electrophysiological responses too, but it is not behaviourally active [ 357 ]. In medfly, ME has been shown to induce poor behavioural responses in binary choice bioassays, while o -eugenol was instead strongly attractive [ 302 ].…”
Section: Volatile Pheromonesmentioning
confidence: 99%